Risk assessment and mechanism of rock burst for deep soft coal roadways - Xinyuan Tian; Linming Dou; Shun Hu; Xiaotao Ma; Fangzhou Lu (Scientific Reports)
Abstract The occurrence of rock burst is related to the physical properties of coal-bearing strata. Under the same mining conditions, the excavation of soft coal seams at 1000 m or deeper has a lower risk of rock burst. The characteristics of rock burst in soft coal seams include a small impact influence range, large roadway deformation, and serious damage to roadway supporting components. This study examines the stress evolution and deformation response of deep and soft coal seams during mining, proposes the impact hazard factor on the basis of numerical simulation results, which takes into account the mining stress and the in-situ stress, substantiates that rock burst in a deep, soft coal seam is unlikely to occur in the absence of dynamic load. Concurrently, a static load model of the roadway surrounding rock is established, and in conjunction with the characteristics of a soft coal structure with poor integrity and low strength, the impact type of roadway is determined as the ‘high static load + low dynamic load’ type.